2006
DOI: 10.1152/ajpcell.00439.2005
|View full text |Cite
|
Sign up to set email alerts
|

Leptin and CCK modulate complementary background conductances to depolarize cultured nodose neurons

Abstract: -We have previously reported that intraceliac infusion of leptin induces a reduction of meal size that depends on intact vagal afferents. This effect of leptin is enhanced in the presence of cholecystokinin (CCK). The mechanisms by which leptin and CCK activate vagal afferent neurons are not known. In the present study, we have begun to address this question by using patch-clamp electrophysiological techniques to examine the mechanisms by which leptin and CCK activate cultured vagal afferents from adult rat no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 36 publications
0
27
1
Order By: Relevance
“…In this study, we delineated the intracellular mechanisms by which CCK-8 interacts with leptin to enhance NG excitation through STAT3 signaling. STAT3 usually acts by stimulating the transcription of target genes (33), but the rapid electrophysiological effects that were observed in this study and that have been reported by others (24,29,34) are not likely to be explained by STAT3-mediated transcription. It is possible that STAT3 may be involved in modifying the activity of channels or receptors.…”
Section: Discussioncontrasting
confidence: 45%
“…In this study, we delineated the intracellular mechanisms by which CCK-8 interacts with leptin to enhance NG excitation through STAT3 signaling. STAT3 usually acts by stimulating the transcription of target genes (33), but the rapid electrophysiological effects that were observed in this study and that have been reported by others (24,29,34) are not likely to be explained by STAT3-mediated transcription. It is possible that STAT3 may be involved in modifying the activity of channels or receptors.…”
Section: Discussioncontrasting
confidence: 45%
“…Furthermore, leptin rapidly increased cytosolic calcium in vagal afferent neurons and this signal was synergistically enhanced by the presence of CCK (29). Using patch-clamp electrophysiological studies, these investigators demonstrated that leptin reversibly depolarized a subpopulation of cultured nodose neurons, many of which were also activated by CCK (31). These function studies suggest that vagal afferent neurons are potential targets for leptin-CCK interaction for the control of satiety.…”
Section: Discussionmentioning
confidence: 96%
“…Much of the vagal NANC inhibitory effect on the stomach is mediated by the release of nitric oxide onto gastric smooth muscle (1,10,24,37,41,44,45,68). Perfusion with CCK-8s induces an excitation in most neurons, including identified gastrointestinal-projecting DMV neurons (4,7,13,23,38,47,48,65,66,75,79). The excitatory effects of CCK-8s on vagal motoneurons imply that the gastroinhibition induced by brain stem apposition of CCK-8s is likely due to activation of the NANC vagal pathway rather than withdrawal of the vagal cholinergic pathway.…”
Section: Discussionmentioning
confidence: 99%